Biotransformation of Cobicistat: Metabolic Pathways and Enzymes - Wang, Pengcheng; I. Shehu, Amina; Liu, Ke; Lu, Jie; Ma, Xiaochao (Drug Metabolism Letters, 2016)
Background: Cobicistat (COBI) is a pharmacoenhancer for antiretroviral therapy. Objective: The current study was designed to profile the metabolic pathways of COBI and to determine the enzymes that contribute to COBI metabolism. Method: We screened COBI metabolites in mice and human liver microsomes. We also used cDNAexpressed human cytochromes P450 (CYPs) to explore the role of human enzymes in COBI metabolism. Results: Twenty new and three known metabolites of COBI were identified in mouse urine and feces. These new metabolic pathways of COBI include glycine conjugation, N-acetyl cysteine conjugation, morpholine ring-opening, and thiazole ring-opening. Twelve of COBI metabolites were further confirmed in mouse and human liver microsomes, including nine new metabolites. Consistent with the previous report, CYP3A4 and CYP2D6 were determined as the major enzymes that contribute to COBI metabolism. Conclusion: This study provided a full map of COBI metabolism. These results can be used to manage CYP-mediated drug-drug interactions and adverse drug reactions that are associated with COBI-containing regimens in human.
Keywords: drug metabolism